Analysis Feasibility of Industrial Business Furniture (Study Case: UD Wooden Furniture. Ray Dawn Subdistrict Marawola ) - Yosep Sompotan; Novita Sari; Mohamad Ichwan; Rita Yunus; Santi Yunus (ProBisnis : Jurnal Manajemen, 2024)
Furniture Ray Dawn produces business​ doors, frames, and windows. This research aims to analyze income and eligibility for UD business. Furniture Ray Dawn. Method data analysis includes revenue analysis and revenue/cost ratio analysis. The research results show the average acceptance of UD business. Furniture Ray Dawn IDR 33,500,000 / month. With total production costs as big as Rp. 16,335,662 . The production costs consist of fixed costs as big as IDR 305,662 and variable as big as IDR 16,030,000 / month. From data analysis, it was determined that UD earned income. Furniture Ray Dawn is as big as IDR 17,164,338 / month. Based on calculation appropriateness effort (R/C Ratio), a value (R/C Ratio) of Rp was obtained. 2.05 or 2.05 > 1, meaning that every cost incurred Rp1 produce income as big as Rp2.05 . So it can be seen that the UD Furniture Business. Ray Dawn is worth trying or running.